Sistem Informasi Web untuk Meningkatkan Kolaborasi Kerjasama Media Diskominfo Bandar Lampung - Adifatillah, Bunga; Sahlinal, Dwirgo; Zuriati, Zuriati (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2024)
One of the main tasks and functions (Tupoksi) of Communications and Informatics Department of Bandar Lampung City (DISKOMINFO) in the field of information and communication is implementing policies and establishing the authority of the city government through collaboration with the mass media. Proposing cooperation by the mass media requires representatives of the media to come to DISKOMINFO of Bandar Lampung City and meet with Public Relations to propose for cooperation. Furthermore, the Public Relations department will manage the incoming proposal data. Collaboration data management still uses Microsoft Excel which allowing for data redundancy. Therefore, a system that can manage this collaboration data is really needed. The aim of this research is to produce a Web-Based Collaboration Information System at DISKOMINFO of Bandar Lampung City which can make it easier for department heads to monitor the collaboration proposal process, make it easier for Public Relations to manage collaboration proposal data and make it easier for the media in the process of submitting collaboration proposals.